2001
DOI: 10.1046/j.1461-0248.2001.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory growth and competitive ability of an invasive weed are enhanced by soil fungi and native neighbours

Abstract: Compensatory responses to herbivory by invasive weeds may foil attempts to arrest their spread with biological controls. We conducted an experiment to study the effects of defoliation and soil fungi on interactions between Centaurea melitensis, an invasive annual from Eurasia, and Nassella pulchra, a native Californian bunchgrass. Defoliation of C. melitensis reduced its final biomass in all species–fungicide treatments, except when C. melitensis was grown with both Nassella and non‐treated soil fungi at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 37 publications
8
79
3
Order By: Relevance
“…For example, the invasive species Centaurea melitensis was larger when grown in competition than when grown alone, but only with AMF present (Callaway et al 2001), suggesting a direct invasive plant benefit from CMN formation through "mycorrhizal-mediated parasitism" (Callaway et al 2001, Bray et al 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the invasive species Centaurea melitensis was larger when grown in competition than when grown alone, but only with AMF present (Callaway et al 2001), suggesting a direct invasive plant benefit from CMN formation through "mycorrhizal-mediated parasitism" (Callaway et al 2001, Bray et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…The mycorrhizal symbiosis is capable of altering competitive interactions between plants (Moora and Zobel 1996, Casper and Castelli 2007, Wagg et al 2011, including invasive plants, both with conspecifics and native competitors (Goodwin 1992, Marler et al 1999, Callaway et al 2001, Bray et al 2003. Potential mechanisms for competitive alteration include plant-soil feedbacks (Bever et al 1997) and either resource sharing or competition through common mycelial networks that connect multiple plants (Hart et al 2003, Selosse et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, removing AMF from tall grass prairie soil promoted plant coexistence because the dominant grasses were more mycorrhizal dependent than were subdominant species [21,22]. Similarly, experimental removal of AMF promoted coexistence by reducing the ability of mycorrhizal-dependent Centaurea maculosa to invade native grasslands of western North America [23,24], and of Medicago minima to invade an Australian grassland [25].…”
mentioning
confidence: 99%
“…hasata, to compensate for herbivory through soil shading. Callaway et al (2001) suggested that the presence of soil fungi and the co-occurring native species Nassella pulcbra promoted a compensatory response of the invasive species Centaurea melitensis to herbivory. Parmesan (2000) reported that herbivory by the butterfly Euphydryas editha reduced fitness of the native montane annual Collinsia torreyi at low density, but not at high density.…”
Section: Con-specific Facilitation Of An Invasive Plantmentioning
confidence: 99%